RAJOITUSTOIMENPITEET LASTENSUOJELULAITOSTEN ARJESSA: KESKIÖSSÄ PÄÄTÖKSENTEKO JA PÄÄTÖSTEN TOIMEENPANO. - Niemi, Minna; Eriksson, Pia (Janus, 2026)
The article examines restrictive measures in Finnish child welfare, 1) exploring the factors influencing decisions regarding such me- asures and 2) the reasoning and implementation of decision-making processes. The study is contextualized in out-of-home care research and the analysis utilizes the decision-making ecological framework. The data consists of six group interviews conducted in residential care units. According to the findings from the content analysis, situations requiring restrictions demand strong expertise and a balance between guidance and restriction. Professionals perceive restrictive measures as both effective and, at times, inadequate or unclear in their application practices. Immediate influences on decisions related to restrictive measures include external factors (e.g., legislation) and case factors (e.g., the child’s individual circumstances). Indirect factors supporting decision-making include organizational and decision-making factors (e.g., strengthening expertise).